Development of a RPA-CRISPR-Cas12a Assay for Rapid, Simple, and Sensitive Detection of Mycoplasma hominis - Chen, Jialing; Huang, Yinger; Xiao, Bin; Deng, Hao; Gong, Kunxiang; Li, Kun; Li, Linhai; Hao, Wenbo (Frontiers in Microbiology, 2022)
Abstract Mycoplasma hominis is one of the smallest pathogens in the human genitourinary tract causing urogenital infections, which is difficult to culture and identify by ordinary methods. CRISPR-Cas12a-based detection system might provide a novel application for M. hominis nucleic acid detection in molecular diagnostics. A plasmid containing the glyceraldehyde-3-phosphate dehydrogenase gene of M. hominis (ATCC_27545) as the positive control was constructed by homologous recombination. The active Cas12a protein was purified by affinity chromatography. The primers for recombinase polymerase amplification (RPA), the CRISPR RNA (crRNA), and the ratio of Cas12a and crRNA were further optimized. Finally, the sensitivity, specificity, and clinical effectiveness of the Cas12a detection system were confirmed. We successfully constructed and optimized a novel nucleic acid detection system for M. hominis based on RPA-CRISPR-Cas12a and the whole process takes only 1 hour. The limit of detection for the gap gene of M. hominis was 3 copies/µL and no cross-reactivity with other urogenital pathogens appeared. In the evaluation of 111 clinical samples, the sensitivity and specificity were both 1.000 and the area under the curve of the receiver operating characteristic was 1.000 (p < 0.001), indicating that the RPA-Cas12a-fluorescent assay was fully comparable to the traditional culture method. Finally, the RPA-Cas12a detection system can also be combined with lateral flow strips (LFS) to achieve visual detection. We successfully developed a low-cost and rapid detection method of M. hominis based on RPA-Cas12a technology. This method realized by fluorescence value readout and visual detection by LFS could be applied in population screening and resource-limited conditions.